Pengaruh Media Komik Visual terhadap Motivasi Belajar Siswa Ditinjau dari Gender Berbeda - Jannah, Husnul; Primawati, Sri Nopita; Sukri, Akhmad; Wahyuni, Bq. Sri; Masiah, Masiah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This research examines the influence of visual comic media on student learning motivation based on different genders. The study applies visual comic media to investigate whether there are differences in learning motivation between male and female students. The activities were conducted at SD Negeri 1 Malaka, North Lombok Regency, involving a total of 45 students. The research utilized a pre-experimental design with a pre-test and post-test design within a single treatment group. The instrument used was a motivation questionnaire based on the ARCS model, covering aspects of attention, relevance, satisfaction, diligence, self-reliance, and self-confidence. The analysis results indicate significant differences in the attention and diligence aspects. Furthermore, female students showed higher motivation compared to male students. These findings indicate that demographic factors such as gender influence responses to learning media such as visual comics. This suggests a need to consider gender factors in the design of visual learning media to achieve maximum effectiveness in learning, particularly in enhancing student learning motivation.